2017
DOI: 10.1016/j.ijrefrig.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of ejector-equipped Joule–Thomson refrigerator operating below 77 K

Abstract: The lowest attainable refrigeration temperature of a nitrogen based Joule-Thomson refrigerator is generally limited to 77 K since the compressor suction pressure is usually higher than atmospheric pressure. The Joule-Thomson process with an ejector is proposed to achieve a refrigeration temperature as low as 68 K by adjusting the evaporation pressure down to 28 kPa and boosting the return stream pressure up to 147 kPa. A one-dimensional numerical model is developed to predict the performance of the ejector at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Since the working fluid may condense and thus disturb the performance of the ejector at low temperatures, the optimum ejector position remained an open question. Lee et al [40] designed an ejector-equipped JT cooler operating at 68 K using nitrogen as the working fluid. The analysis showed that the corresponding evaporation pressure of 28 kPa could be realized through the ejector.…”
Section: Utilization Of Ejectors In Jt Cryocoolersmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the working fluid may condense and thus disturb the performance of the ejector at low temperatures, the optimum ejector position remained an open question. Lee et al [40] designed an ejector-equipped JT cooler operating at 68 K using nitrogen as the working fluid. The analysis showed that the corresponding evaporation pressure of 28 kPa could be realized through the ejector.…”
Section: Utilization Of Ejectors In Jt Cryocoolersmentioning
confidence: 99%
“…Most of these studies focused on conceptual designs or experimental investigations of the use of ejectors in JT cooling cycles. Yu et al [35][36][37], Rashid et al [38], Cao et al [39] and Lee et al [40] analyzed the improved performance of JT cooling cycles with an additional ejector. In these analyses, entrainment ratios and the pressure lift ratios of ejectors were assumed or derived based on mass, momentum and energy conservation, taking into account the assumed efficiencies of the nozzle, mixing section and diffuser.…”
Section: Utilization Of Ejectors In Jt Cryocoolersmentioning
confidence: 99%
“…The use of ejectors in cryogenic cooling systems was first proposed by Rietdijk [8] for creating subatmospheric pressure in a liquid helium evaporator to achieve a cooling temperature lower than 4.2 K. Afterwards, helium ejectors were further studied by Haisma [9], Nicholds [10], Agapov et al [11], Wu et al [12], Vonrohr and Trepp [13], Johnson and Daggett [14]. Moreover, ejectors operating with other gases, such as hydrogen gas [15] and nitrogen gas [16][17][18][19] have also been investigated. However, the above mentioned studies focused on conceptual designs or experimental investigations and only a few studies on the theory of ejectors exist.…”
Section: Introductionmentioning
confidence: 99%
“…However, the above mentioned studies focused on conceptual designs or experimental investigations and only a few studies on the theory of ejectors exist. Yu et al [20], Rashid et al [21] and Lee et al [19] presented the thermodynamic analysis of the overall performance improvement due to the introduction of ejectors into cryogenic cooling systems. In these analyses, the ejector performance is estimated by using thermodynamic modeling, in which the ejector is divided into a motive nozzle, a mixing section, and a diffuser.…”
Section: Introductionmentioning
confidence: 99%
“…3.6, can enable other innovative ideas. For example, they can increase the performance of novel ejector-based systems and serve as a cryogenic current lead for small-and large-scale superconducting systems [49,50].…”
Section: Introductionmentioning
confidence: 99%